Knowledge Of Palliative Care Amongst Undergraduate Medical Students in Rural Medical College of Maharashtra - Bogam, Rahul R; Kumbhar, Shekhar M; Sahu, Sonali B; Mane, Amol S; Sagare, Sunil M; Chowdhury, Yuvraj Singh (National Journal of Community Medicine, 2012)
Introduction: The introduction of palliative care in undergraduate medical and nursing training is a necessary step in the development of formal system of education and registration of palliative care in India. The present study attempted to understand the knowledge of underdergraduate medical students pertaining to various aspects of palliative care. Material and Methods: A structured modified pretested self administered questionnaire on palliative care was used to collect information. Results: Overall poor knowledge (Mean score = 8.11 out of 17) was observed regarding palliative care. Good knowledge was observed amongst students regarding certain aspects like comprehensive approach of palliative care as 102(93.57%) students correctly stated that palliative care approach promotes not only physical but also psychosocial and spiritual well being. Nearly all (99.08%) students were well versed with components of good communications skills. Conclusion: The study revealed inadequacies in the knowledge of undergraduate medical students pertaining to palliative care.